2022
DOI: 10.1155/2022/4923277
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Great Plantain (Plantago major L.) in the Treatment of Second-Degree Burn Wounds: A Case-Control Study

Abstract: Background. Great plantain (Plantago major L. or P.major) is a medicinal plant that is available all around the world. The whole plant has several bioactive compounds including terpenoids, flavonoids, phenolic compounds, alkaloids, fatty acids, iridoid glycosides, polysaccharides, and vitamins. Scientific studies have recognized several medical benefits like wound healing, anti-inflammatory, antimicrobial, antiulcerative, and antioxidative agents. The wound-healing capacity of this plant has been investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The wound-healing capacity of the leaf extract has been proved by "in vivo" tests with animals and humans, using different pharmacology forms, such as ointment [30] and topical gel [31].…”
Section: Introductionmentioning
confidence: 99%
“…The wound-healing capacity of the leaf extract has been proved by "in vivo" tests with animals and humans, using different pharmacology forms, such as ointment [30] and topical gel [31].…”
Section: Introductionmentioning
confidence: 99%
“…The average complete healing time in the P. major and control groups was 11.73 d and 13 d, respectively. The study discovered that P. major ointment is a safe and efficient herbal product for the treatment of second-degree burn wounds since it not only cures the lesion but also serves as an analgesic and antibacterial agent[ 138 ]. Ghanadian et al [ 125 ] conducted a clinical study where patients with DFU or pressure ulcers were randomly assigned to medication ( P. major ) or control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Plantago major contains a number of active substances, including caffeic acid derivatives, polysaccharides, terpenoids, lipids, and flavonoids, as is shown in Table 3 [ 82 ]. A safe and effective herbal remedy for the treatment of second-degree burn wounds is P. major ointment, which not only contains qualities for healing wounds but also functions as an analgesic and an antibacterial agent [ 83 ]. Furthermore, it was found that, when compared to alternative therapies, P. major extract effectively accelerated the healing of dorsal cervical injuries in mice [ 84 ].…”
Section: Plant Species and Their Potential Therapeutic Interestsmentioning
confidence: 99%